Resin-dependent mechanical anisotropy in laser vat photopolymerization correlates to the initial rate of polymerization and critical energy - Dagoberto Torres-Alvarez; Angel Celis-Guzman; Alan Aguirre-Soto (Additive Manufacturing Letters)
The degree of mechanical anisotropy in objects printed with laser vat photopolymerization (VPP) remains controversial. It has been stated that objects with a higher degree of mechanical isotropy are produced with VPP as compared to other polymer-based additive manufacturing techniques, such as fused filament fabrication (FFF). However, reports on the evaluation of resin-dependency of the mechanical anisotropy obtained with VPP are scarce. Furthermore, the degree of anisotropy (DA) was quantified using different procedures. Here, six commercial resins were selected to evaluate how the DA correlates to the initial rate of polymerization (RP0), critical energy (EC), and penetration depth (DP) for materials with a broader range of properties. State-of-the-art procedures to calculate the degree of mechanical anisotropy are discussed, and an ideal method is proposed, namely, the ratio of the standard deviations related to the inter- and intra-layer forces: DA=(sdinter/sdintra). The elastic modulus (E) was confirmed isotropic with the three resins that were previously reported. However, objects printed with the additional resins that polymerize at higher initial rates (RP0 =72.1 mM/s) and with lower critical energies (EC = 0.36 mJ/cm2) appear more anisotropic. A linear trend was obtained for the scaling of the mechanical DA with RP0. Moreover, a logarithmic correlation between EC and the DA in E was found, which appears inappropriate for EC as a function of the DA in the maximum stress (σMax). This study aims to spur research on the mechanisms underlying the dependence of the mechanical DA on the resin-curing behavior for objects fabricated by VPP.